Experimental and Theoretical Reduction Potentials of Some Biologically Active Ortho-Carbonyl Para-Quinones - Salazar-Gonzalez, R (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
The rational design of quinoneswith specific redox properties is an issue of great interest because of their applications in pharmaceutical and material sciences. In this work, the electrochemical behavior of a series of four p-quinones was studied experimentally and theoretically. The first and second one-electron reduction potentials of the quinones were determined using cyclic voltammetry and correlated with those calculated by density functional theory (DFT) using three different functionals, BHandHLYP, M06-2x and PBE0. The differences among the experimental reduction potentials were explained in terms of structural effects on the stabilities of the formed species. DFT calculations accurately reproduced the first one-electron experimental reduction potentials with R2 higher than 0.94. The BHandHLYP functional presented the best fit to the experimental values (R2 = 0.957), followed by M06-2x (R2 = 0.947) and PBE0 (R2 = 0.942). © 2017 by the Authors.